2019
DOI: 10.1093/mnras/stz2204
|View full text |Cite
|
Sign up to set email alerts
|

Time-slicing spiral galaxies with SDSS-IV MaNGA

Abstract: Spectra of galaxies contain a wealth of information about the stellar populations from which they are made. With integral-field unit (IFU) surveys, such data can be used to map out stellar population properties across the face of a galaxy, allowing one to go beyond simple radial profiles and study details of non-axisymmetric structure. Todate, however, such studies have been limited by the quality of available data and the power of spectral analysis tools. We now take the next step and study the barred spiral … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…In the literature, bars have been found to be more metal-rich and less α-enhanced than their surrounding discs by Neumann et al (2020), while Carrillo et al (2020) found that the bar in NGC 2903 has similar metallicity and a higher fraction of younger stars than the outer disc, which they interpreted as evidence that gas flowing along the bar has triggered more recent star-formation activity. Further evidence for ongoing star-formation along the leading edges of bars in spiral galaxies has also been found by Peterken et al (2019) andFraser-McKelvie et al (2020). In the sample of unbarred S0s used in this work, we found that the lenses tend to have higher metallicities than discs, while the discs display more recent or longer episodes of star formation than the lenses.…”
Section: Mass-weighted Stellar Populationssupporting
confidence: 82%
“…In the literature, bars have been found to be more metal-rich and less α-enhanced than their surrounding discs by Neumann et al (2020), while Carrillo et al (2020) found that the bar in NGC 2903 has similar metallicity and a higher fraction of younger stars than the outer disc, which they interpreted as evidence that gas flowing along the bar has triggered more recent star-formation activity. Further evidence for ongoing star-formation along the leading edges of bars in spiral galaxies has also been found by Peterken et al (2019) andFraser-McKelvie et al (2020). In the sample of unbarred S0s used in this work, we found that the lenses tend to have higher metallicities than discs, while the discs display more recent or longer episodes of star formation than the lenses.…”
Section: Mass-weighted Stellar Populationssupporting
confidence: 82%
“…We use the full-spectrum stellar population fitting code STARLIGHT (Cid Fernandes et al 2005) to derive a best-fit spectrum, created from a linear combination of a set of input single stellar population (SSP) template spectra -with no assumptions or restrictions on the shape of the derived star formation histories -and an applied dust attenuation. The fitting method used is similar to that used by Peterken et al (2019), and is described fully by Peterken et al (in prep.). Here we highlight the key relevant details.…”
Section: Measuring Dust Attenuation From Stellar Population Modellingmentioning
confidence: 99%
“…as was done by Peterken et al (2019a) for a spiral arm]. Peterken et al (2019b) used both bar and spiral masks from GZ:3D for the galaxy MCG + 07-28-064 to demonstrate a new technique of reconstructing spatially resolved star formation histories from MaNGA data cubes. The bar (and spiral arm) masks were used as a visual indication of where these features are relative to features in stellar population metallicity as a function of age.…”
Section: Bar Regionsmentioning
confidence: 99%